Micro and nano plastics: contaminants in beverages and prevention strategies - Ma, Chang; Ramachandraiah, Karna; Jiang, Guihun (Frontiers in Sustainable Food Systems, 2024)
The widespread use of plastics in beverage packaging has led to the accumulation of microplastics (MPs) and nanoplastics (NPs) in beverages, which poses significant environmental and health hazards. This review explores the sources, entry pathways, and risk factors for MPs and NPs in beverages, emphasizing their toxicological profiles and harmful effects on human health and the environment. Methods for detecting MPs and NPs in beverages are discussed, highlighting the need for standardized testing protocols. Furthermore, future solution strategies, challenges, and preventive measures for mitigating MP and NP contamination in beverages are proposed, including advanced filtration systems, the development of alternative packaging materials, and the strengthening of regulatory standards. Collaborative efforts among industry stakeholders, scientific institutions, and policymakers are essential to address this complex issue and ensure the safety and purity of beverages for consumers worldwide.